Determination of dihydromyricetin in rat plasma by LC-MS/MS and its application to a pharmacokinetic study. (1st January 2017) - Liu, Lu; Yin, Xiaolan; Wang, Xu; Li, Xiaohua
Abstract: Context: The pharmacokinetics properties of dihydromyricetin (DHM) are still unknown. Objective: This study investigates the pharmacokinetic characteristics of DHM using a sensitive and reliable LC-MS/MS method. Materials and methods: A rapid and sensitive LC-MS/MS method was developed for the determination of DHM in male Sprague–Dawley rat plasma. Twelve rats were equally randomized into two groups, including the intravenous group (2 mg/kg) and the oral group (20 mg/kg). Blood samples (250 μL) were collected at designated time points and analyzed using this method. The pharmacokinetic parameters were calculated using DAS 3.0 pharmacokinetic software. Results: The calibration curve was linear within the range of 0.5–200 ng/mL ( r > 0.998) with the lower limit of quantification at 0.5 ng/mL. After the intravenous injection, DHM reached a maximum concentration of 165.67 ± 16.35 ng/mL, and t 1/2 was 2.05 ± 0.52 h. However, DHM was not readily absorbed and reached C max 21.63 ± 3.62 ng/mL at approximately 2.67 h following the oral administration of DHM, and t 1/2 was 3.70 ± 0.99 h. The MRT for the intravenous group and the oral group were 2.62 ± 0.36 and 5.98 ± 0.58 h, respectively. The AUC (0-t) for the intravenous group and the oral group were 410.73 ± 78.12 and 164.97 ± 41.76 ng·L/mL, respectively, so the absolute bioavailability of DHM was 4.02% which was poor. Discussion and conclusion: The results indicated that the bioavailability was poor. Further work needs to be conducted to investigate the reason for poor bioavailability and improve this situation.